(3JPjjd CQLhRI GHf SjfG aj GdMejGJs - (3CHi ehSi gGQhf Hf ESMGb Hf YRQhfs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdbGOQ GdOGFe GdaQO GdMcje GdaGWQ hgPg CQLhRI fXeJgG hai VQhH GdMejGJ UaJgG s
(3BNQgG (B:s
(3hGSJYed GdJMdjd eG GSJWYfG Jcf HgPG GdaYd bO CUHJG s
(3Vef eLehY s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B52 s
(3eUOQ GbJfGA GdCUd (B:s
(3CSHGfjG (B_ (3eOQjO (B(3/5265) s
Keywords: (3GdWHs